Hubungan Dukungan Sosial dengan Psychological Well-Being pada Santri di Pondok Pesantren Kota Bogor - Habib Priyono Habib Priyono; Annas Alkhowarizmi; Alvin Fachrully Septiano (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Background: Life in Islamic boarding schools (pesantren) requires students (santri) to adapt to new and challenging environments, ranging from separation from family to intensive academic and religious pressures. These conditions potentially affect the students' psychological well-being. Social support from peers, caregivers, and family is believed to be a significant protective factor in maintaining individual well-being. Objective: This study aimed to determine the relationship between social support and psychological well-being among santri in pesantren in Bogor City. Methods: A quantitative cross-sectional design was used. The sample consisted of 214 santri selected through stratified random sampling from three pesantren in Bogor City in 2026. Instruments used were the Social Support Scale by Sarafino & Smith and the Ryff Psychological Well-Being Scale. Data analysis included univariate, bivariate, and Pearson correlation tests. Results: The majority of respondents had high social support (58.4%) and moderate psychological well-being (52.3%). Pearson correlation analysis revealed a significant positive relationship between social support and psychological well-being (r = 0.612; p < 0.001). Conclusion: There is a significant relationship between social support and psychological well-being among santri in Bogor City. Higher social support received by santri corresponds to better psychological well-being. These findings underscore the importance of strengthening social support networks within the pesantren ecosystem as a mental health promotion strategy.